A role for enhanced functions of sleep in psychedelic therapy?. (June 2018) - Froese, Tom; Leenen, Iwin; Palenicek, Tomas
After a hiatus of several decades, there has been a resurgence of studies into the therapeutic potential of serotonergic psychedelics. When administered in controlled settings, they have been reported to induce a wide variety of long-lasting positive psychological changes. However, the mechanisms by which psychedelics impart these long-lasting benefits remain poorly understood. Here, we highlight one possibility that has remained underexplored: a beneficial interaction with the self-optimizing functions of sleep.